Aberrant Lipid Metabolism in Macrophages Is Associated with Granuloma Formation in Sarcoidosis - Lim, Clarice X.; Redl, Anna; Kleissl, Lisa; Pandey, Ram Vinay; Mayerhofer, Carolina; El Jammal, Thomas; Mazic, Mario; Gonzales, Karine; Sukhbaatar, Nyamdelger; Krausgruber, Thomas; Bock, Christoph; Hengstschläger, Markus; et al. (American journal of respiratory and critical care medicine, 2024)
Chronic sarcoidosis is a complex granulomatous disease with limited treatment options that can progress over time. Understanding the molecular pathways contributing to disease would aid in new therapeutic development. To understand whether macrophages from patients with nonresolving chronic sarcoidosis are predisposed to macrophage aggregation and granuloma formation and whether modulation of the underlying molecular pathways influence sarcoidosis granuloma formation. Macrophages were cultivated from isolated peripheral blood CD14 monocytes and evaluated for spontaneous aggregation. Transcriptomics analyses and phenotypic and drug inhibitory experiments were performed on these monocyte-derived macrophages. Human skin biopsies from patients with sarcoidosis and a myeloid -specific sarcoidosis mouse model were analyzed for validatory experiments. Monocyte-derived macrophages from patients with chronic sarcoidosis spontaneously formed extensive granulomas compared with healthy control participants. Transcriptomic analyses separated healthy and sarcoidosis macrophages and identified an enrichment in lipid metabolic processes. patient granulomas, sarcoidosis mouse model granulomas, and those directly analyzed from lesional patient skin expressed an aberrant lipid metabolism profile and contained increased neutral lipids. Conversely, a combination of statins and cholesterol-reducing agents reduced granuloma formation both and in a sarcoidosis mouse model. Together, our findings show that altered lipid metabolism in sarcoidosis macrophages is associated with its predisposition to granuloma formation and suggest cholesterol-reducing therapies as a treatment option in patients.